Towards low loss non-volatile phase change materials in mid index waveguides. Issue 1 (23rd August 2021) - Faneca, Joaquin; Zeimpekis, Ioannis; Ilie, S T; Bucio, Thalía Domínguez; Grabska, Katarzyna; Hewak, Daniel W; Gardes, Frederic Y
Abstract: Photonic integrated circuits currently use platform intrinsic thermo-optic and electro-optic effects to implement dynamic functions such as switching, modulation and other processing. Currently, there is a drive to implement field programmable photonic circuits, a need which is only magnified by new neuromorphic and quantum computing applications. The most promising non-volatile photonic components employ phase change materials such as GST and GSST, which had their origin in electronic memory. However, in the optical domain, these compounds introduce significant losses potentially preventing a large number of applications. Here, we evaluate the use of two newly introduced low loss phase change materials, Sb2 S3 and Sb2 Se3, on a silicon nitride photonic platform for future implementation in neuromorphic computing. We focus the study on Mach–Zehnder interferometers that operate at the O and C bands to demonstrate the performance of the system. Our measurements show an insertion loss below 0.04 dB μm −1 for Sb2 S3 and lower than 0.09 dB μm −1 for Sb2 Se3 cladded devices for both amorphous and crystalline phases. The effective refractive index contrast for Sb2 S3 on SiNx was measured to be 0.05 at 1310 nm and 0.02 at 1550 nm, whereas for Sb2 Se3, it was 0.03 at 1310 nm and 0.05 at 1550 nm highlighting the performance of the integrated device.